2021
DOI: 10.1002/pd.5890
|View full text |Cite
|
Sign up to set email alerts
|

Increased RISK for 47,XXY on cell‐free DNA screen: Not always Klinefelter syndrome

Abstract: Key Points What's already known about this topic? Noninvasive cell‐free DNA (cfDNA) tests allow prenatal identification of high risk for Klinefelter syndrome cfDNA test requires a prenatal or postnatal confirmation to reach a definitive diagnosis What does this study add? In a significant number of cfDNA tests, results reporting increased risk for 47, XXY were not confirmed on diagnostic testing Invasive procedures must always be discussed to exclude chromosomal variations with a more severe phenotype

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In the study by Ronzoni et al, four cases presented with mosaic forms of SCAs in the pre-or postnatal follow-up after cellfree NIPT showed an increased risk of Klinefelter syndrome in the fetus (Ronzoni et al, 2021). Various grades of mosaicism (47,XXY/46,XY) is known to be present in 10-20% of Klinefelter males and these individuals tend to present with a milder form of the syndrome (Kanakis and Nieschlag, 20182018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the study by Ronzoni et al, four cases presented with mosaic forms of SCAs in the pre-or postnatal follow-up after cellfree NIPT showed an increased risk of Klinefelter syndrome in the fetus (Ronzoni et al, 2021). Various grades of mosaicism (47,XXY/46,XY) is known to be present in 10-20% of Klinefelter males and these individuals tend to present with a milder form of the syndrome (Kanakis and Nieschlag, 20182018).…”
Section: Discussionmentioning
confidence: 97%
“…The PPV for Klinefelter syndrome in twin pregnancies is unknown. In a recent study, Ronzoni et al performed prenatal or postnatal karyotyping after cell-free NIPT suggested an increased risk of 47,XXY in 34 pregnancies ( Ronzoni et al, 2021 ). In nine cases the cell-free NIPT result was not confirmed and in one third of these cases the fetus had a normal 46,XY karyotype corresponding to a false-positive rate of 8.8%.…”
Section: Discussionmentioning
confidence: 99%
“…These 5 discordant results represent the imperative need for prenatal genetic counseling on NIPT results positive for SCAs to also include the possibility for an SCA diagnosis that is abnormal but discordant with the NIPT lab result. In a recent study this concern is articulated specific to NIPT results positive for 47,XXY, with the authors underlining the importance of a definitive diagnosis not only for excluding a false positive but also excluding other chromosomal variations which may have a different and more severe phenotype (Ronzoni et al, 2020). Our study findings reinforce the importance of counseling regarding possible other SCAs as there are significant phenotypic differences associated with higher risks of medical complexity and neurodevelopmental involvement when comparing sex chromosome trisomies vs. pentasomies, such as 48,XXYY (Raznahan et al, 2018; Skuse, Printzlau, & Wolstencroft, 2018; N.…”
Section: Discussionmentioning
confidence: 99%
“…For these and other reasons, NIPS remains classified as a screening, nondiagnostic test with standard recommendations that any positive NIPS result be followed by confirmatory diagnostic testing (Devers et al, 2013;Hartwig et al, 2017). However, five of our nine discord- severe phenotype (Ronzoni et al, 2021). Our study findings reinforce the importance of counseling regarding possible other SCAs as there are significant phenotypic differences associated with higher risks of medical complexity and neurodevelopmental involvement when comparing sex chromosome trisomies vs. tetrasomies, such as 48,XXYY (Raznahan et al, 2018;Skuse et al, 2018;Tartaglia et al, 2011Tartaglia et al, , 2012.…”
Section: Practice Implicationsmentioning
confidence: 99%